On the ground spider genera Marjanus gen. n., Lasophorus gen. n. and Turkozelotes Kovblyuk & Seyyar, 2009 (Araneae: Gnaphosidae) from Greece - Chatzaki, Maria (Zootaxa, 2018)
New taxonomic data on the ground spiders of the family Gnaphosidae from Greece are presented. Two genera are proposed as new to science (Marjanus gen. n. and Lasophorus gen. n.) together with two new species (Lasophorus zakkak sp. n. and Lasophorus zografae sp. n.) and a new combination (Marjanus platnicki comb. nov.). Additionally the genus Turkozelotes Kovblyuk & Seyyar, 2009 is here rediagnosed and the female of the type species T. microb Kovblyuk & Seyyar, 2009 is described for the first time. The finding of the matching male of Setaphis mccowani Chatzaki & Russell-Smith, 2017 suggests the transfer of this species to Turkozelotes and hence the male of T. mccowani comb. nov. is described for the first time. Taxonomic affinities of these genera and species are discussed.